Nacionalinės bibliografijos navigacijos veikia!? - Bliūdžiuvienė, Nijolė; Cicėnienė, Rima; Gieda, Aurelijus; Žaltauskaitė, Vilma; Šeina-Vasiliauskienė, Viktorija; Petreikis, Tomas; Tiukšienė, Zita; Misiūnas, Remigijus; Budriūnienė, Jolanta (Colloquia, 2019)
-